Gentlewomen, Fallen Men and Caged Birds: Playing with Victorian Myths in Assassin’s Creed Syndicate - Ines Munker, (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2025)
Emphasizing the “interplay between self-reflexivity and immersion”, the neo-Victorian project allows us to consider a diverse array of creative works that (re)construct Victorian myths (Boehm-Schnittker and Gruss 2011, 15). Assassin’s Creed Syndicate’s approach to immersion through a multi-layered player embodiment renders the “critical interface between the past and present” central to neo-Victorian media tangible for its audience (Kohlke 2008, 1). The game creates a self-reflexive in-between space by implementing an “implied character” as a vessel for a critical re-evaluation of Victorian myths (Aarseth and Karhulahti 2022, 269). Employing a multimodal perspective, this paper analyzes how Assassin’s Creed Syndicate extends beyond popular myths of private and public spheres, the Angel in the House, the fallen woman, the gentleman, the dandy, and Carlyle’s Captains of Industry. Through an alternating gendered perspective, the player co-constructs a neo-Victorian narrative that comments on a range of issues connected to these myths, including women’s education, marriage and motherhood, male rivalries, queer identities, and father-son relationships during the Industrial Revolution. Ultimately, persisting myths of Victorian femininity and masculinity are displaced and re-emerge as imaginings of self-sufficient gentlewomen and fallen men, which, in the neo-Victorian fashion, are colored by contemporary ideas and thus reveal just as much about the Victorians as they do about their lingering influence on our twenty-first-century identities.